International investment rule-making : stocktaking, challenges and the way forward (UN New YorkUS, 2008)
Reviews 60 years of international investment rule-making and identifies main trends in current treaty practice, as well as the core characteristics of the existing universe of international investment agreements at the beginning of the 21st century.
Keywords: INTERNATIONAL INVESTMENT